1988
DOI: 10.1007/bf02106784
|View full text |Cite
|
Sign up to set email alerts
|

Lungenfunktion und Symptome bei Beschäftigten in Geflügelbetrieben

Abstract: Environmental measurements were made in different types of poultry confinement buildings. Levels of total dust 1.6 meters above the ground averaged 5.0 mg/m3. Ammonia levels averaged about 13 ppm with peak values of about 50 ppm. To study possible respiratory problems of the people working in these confinement buildings, the ventilatory lung function was measured and an interrogation concerning respiratory symptoms was carried out by 26 (7 females, 19 males) poultry farmers. A very high prevalence (10 of 26) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
5
0
2
Order By: Relevance
“…Poultry farmers reported the highest level of workrelated symptoms, but due to their small numbers onlỳ`n asal irritation at work'' was signi®cantly elevated. A previous study of Swiss poultry farmers [Danuser et al, 1988] as well as a study from Croatia [Zuskin et al, 1995] showed a high prevalence of acute symptoms during work as well as reduced lung function measurements. Compared with other farming categories, the highest prevalence rate of nasal allergies was seen in poultry farmers.…”
Section: Type Of Farmingmentioning
confidence: 97%
See 1 more Smart Citation
“…Poultry farmers reported the highest level of workrelated symptoms, but due to their small numbers onlỳ`n asal irritation at work'' was signi®cantly elevated. A previous study of Swiss poultry farmers [Danuser et al, 1988] as well as a study from Croatia [Zuskin et al, 1995] showed a high prevalence of acute symptoms during work as well as reduced lung function measurements. Compared with other farming categories, the highest prevalence rate of nasal allergies was seen in poultry farmers.…”
Section: Type Of Farmingmentioning
confidence: 97%
“…Various potential aeroallergens in organic poultry dust, especially from mites and the animal itself, have been described [Lutsky et al, 1984;Mu Èller et al, 1986;Perfetti et al, 1997]. It is known that high concentrations of ammonia and organic dust are found in poultry houses [Danuser et al, 1988]. In poultry con®ne-ment buildings, bacteria, endotoxin, and fungal contaminants are highest compared to different animal con®nements buildings [Seedorf et al, 1998].…”
Section: Type Of Farmingmentioning
confidence: 99%
“…The prevalence of chronic bronchitis, organic dust toxic syndrome (ODTS), and other respiratory diseases is increased among workers in poultry houses (Brown, 1990;Danuser et al, 1988;Leistikow et al, 1989;Rylander, 1986;Thelin et al, 1984;Zuskin et al, 1995). Particularly, the loading and unloading of chickens is reported to be related to high exposure levels (Rylander, 1986).…”
Section: Introductionmentioning
confidence: 93%
“…Die existierenden Untersuchungen zu Gesundheitsrisiken in der Geflügel- [7] und Schafhaltung [22] weisen auf eine hohe Prävalenz von Atemwegssymptomen hin. Expositionsmessungen wurden vereinzelt in Geflügelställen vorgenommen [8,40]. Über die Expositionsbedingungen bei Schafhaltern liegen bisher keine Studien vor.…”
Section: Risikofaktoren Für Atemwegserkrankungen Bei Landwirten In Deunclassified